Women Resistance in Drama Scripts Perempuan Salah Langkah by Wisran Hadi - Rizkiyah Afdhaliyah; Moza Shafira (Widyantara, 2023)
Literary works are a tool to voice women's rights. The presence of literary works can be used as information for readers about the struggles of women's forms of resistance or resistance to the customs and culture that bind them. Wisran Hadi's drama "Perempuan Salah Langkah" is a literary work with Minangkabau culture. Through the character of Sinan, it can be seen the resistance problems she experienced in her attempt to release the stereotype of women that has been rooted in a culture, namely when she tried to voice gender equality. The purpose of this study is to reveal the form of resistance or resistance of women. The approach used in the structural analysis of this drama script is feminist literary criticism, with a review of structural analysis research, and descriptive research methods. The results show that women can put up a fight or resistance to fight back for their rights. Through the female character in Wisran Hadi's drama “Perempuan Salah Langkah”, we can see her struggle to become an independent and independent woman.